The social construction of time and its influence on medical education - Wyatt, Tasha R.; de Oliveira Vidal, Edison Iglesias [UNESP] (Wiley, 2025)
Introduction: Few sociocultural constructs exist that are so deeply embedded in our daily lives and able to influence our thoughts, behaviours and interactions than time itself. Time spans all cultures, and yet many of us have not critically engaged with how time effects what we do, how we perceive and the ways in which we interact. As such, our relationship to time remains almost invisible running in the background nearly unnoticed until it is somehow brought into conscious awareness. Context: In this paper, we draw on Levine's concepts of clock time and event time as different perspectives on time, demonstrating how they play out in medical education and clinical practice within the United States and Brazil. Clock time treats time as something external to our lives, fixed by the natural world and measured by clocks. Event time is conceptualised more flexibly, where the duration of activities depends on internal cues related to the flow and progression of events rather than strict schedules. Discussion: By contrasting these differences, we hope to make visible the way that time influences our choices for educating physicians and provide a foundation for medical education to begin questioning how time is positioned, experienced and understood as a powerful force in the shaping of our profession. Additionally, we consider these perspectives within the concepts of Taylorism and Slow Medicine to better understand their links to medicine's formal and hidden curriculum in hopes of raising awareness and create new visions for medical education.